Kajian Yuridis Perlindungan Hukum Saksi Pelaku Yang Bekerjasama Dalam Undang-Undang Perlindungan Saksi dan Korban - Anggraeni, Surya; Asba, Patahillah; Putra, Moch. Alfatah Alti (Jurnal Litigasi Amsir, 2023)
This study aims to determine the legal protection of witness witnesses who cooperate in the Law on the Protection of Witnesses and Victims. To find out the legal vacuum for the protection of witnesses for perpetrators who cooperate in the law for the protection of witnesses and victims. This study uses the type of normative legal research. The research results show that Law Number 31 of 2014 concerning the protection of witnesses and victims provides protection and assistance to witnesses and victims. The protection that is meant here is as a place of refuge and protection for someone who needs it as a result he feels safe against the threats around him. courts and judges, including the Supreme Court as an institution of judicial power, play an important role in filling the legal vacuum (rechtsvacuum). work together (Justice Collaborator).